Montseny, a sustainable rural policy in the periphery of the Barcelona's metropolitan area - Rafael Balanzo; Agapit Borras (European Regional Science Association (ERSA), 2010)
Spain had build more houses in 2006 than France, Germany and the United Kingdom together. Actually, this urban growth is unsustainable and damage the resources the territory. 'People becomes rich, but the territory becomes poor'. The metropolitan area of Barcelona has growth hard but the rural areas lost there identity and his natural resources. Is not possible an unlimited growth in a limited territory. Montseny is a municipality in the periphery of metropolitan area and inside Natural Park of Montseny and will develop a rural policy for a sustainable growth. CATALONIA 7.4 millions 947 Municipalities, 50% less then 2.000 inhabitants Metropolitan area of Barcelona, 4.5 millions inhabitants Montseny, population 320 inhabitants, area, 9.62 km2 MONTSENY: STRATEGY AND GOALS Strengthen, with facilities, the centrality of the municipality inside the Montseny's valley. To take care of the population, his roots and territory's identity Take part in territorial balance of Catalonia, as Catalan government carry out. To avoid a dependency of economic sectors such as tourism, restaurants and weather seasons and create new economics sources. To introduce and improve the basic facilities that a little village need to fix the people. PROJECTS To diversify the economic framework, the municipality will carry out these projects: Nursery (it is a way to ensure a scholar continuity inside the rural village) (2010) Scholar restaurant (to lunch together besides de primary school (2010) Housing for young people (to help young people to get a house) (2011) Central heating (take profit of natural resources and to save energy) (2014 - ) Offices for enterprising young people (foster training of young) (2010) Slaughterhouse (It is a necessary tool for the municipal economy (2010) Little shops (to improve the mix the urban uses of the village) (2010) Agricultural shop (to sell agricultural foodstuffs direct to buyer (2010) School of shepherds (to ensure the continuity of mountain livestock) (2010) Project for megalithic monument (to protect the megalithic monument) (2010) Old people's home (to ensure quality of life for old people) (2011 -)
Keywords: 330